Factores maternos relacionados con el peso al nacer de recién nacidos a término, Colombia, 2002-2011 (2016)
ABSTRACT: The study aimed to identify maternal factors associated with birth weight in Colombia from 2002 to 2011. This was a descriptive study based on data from the Live Birth Registry of Colombia, Administrative Department of Vital Statistics. Birth weight was classified as low birth weight < 2,500g, insufficient birth weight 2,500-2,999g, normal birth weight 3,000-3,999g, and high birth weight ≥ 4,000g. Data analysis used Mann-Whitney U test, Kruskal-Wallis test, and multinomial logistic regression. Women with increased likelihood of low birth weight newborns were 35 years or older (OR = 1.4; 95%CI: 1.39-1.4), had little schooling (OR = 1.1; 95%CI: 1.1-1.1), were single (OR = 1.1; 95%CI: 1.1-1.2), without prenatal care (OR = 1.9; 95%CI: 1.9-2.0), and lived in rural areas (OR = 1.2; 95%CI: 1.1-1.2). Women with higher prevalence of high birth weight newborns were 35 years or older (OR = 1.1; 95%CI: 1.1-1.1) and had four or more children (OR = 2.1; 95%CI 2.0-2.1). Insufficient birth weight showed a similar pattern to low birth weight. In conclusion, social, demographic, and maternal factors influence the birth weight of newborns in Colombia.